ANALISIS PENGARUH KETERSEDIAAN PEMBIAYAAN, PENGETAHUAN AKUNTANSI, DAN DIGITALISASI TERHADAP KINERJA UMKM DI KOTA BATAM - Rusanto, Patrick; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2025)
The objective of this research is to determine the influence of financing availability, accounting knowledge, and digitalization on the performance of Small and Medium Enterprises (MSMEs). This study employs a quantitative research approach. There are 81,486 MSMEs registered at the Batam City Department of Cooperatives and Micro, Small and Medium Enterprises. The research sample consists of 102 MSMEs, determined using the Slovin formula and selected through simple random sampling. The t-test results indicate that financing availability has no significant effect on MSMEs performance, while accounting knowledge and digitalization have a significant impact on MSMEs performance. Furthermore, the F-test results show that financing availability, accounting knowledge, and digitalization together influence MSMEs performance